Review Artikel Teori Evolusi Sel Prokariotik, Eukariotik dan Penyusun Membran Sel - Citra Bunga Lestari; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
Understanding the evolution of cells is very important, which means studying the development of living things. The smallest structural elements of living things are cells. These cells gradually change both their structure and function. It can be said that almost all biologists can accept the theory of biological evolution or the theory of evolution that continues to develop , even though the theory is based on circumstantial evidence . The principle of this evolutionary theory is that humans, animals, and plants all evolve continuously. This journal is based on the narrative review method and displays a narrative review design from research journals related to the theory of prokaryotic, eukaryotic, and cell membrane-related evolution. The importance of cells continues to develop along with advances in technology and the discovery of sophisticated tools. Until now it is known that the structure and activities of cells are not as simple as previously thought. Cells that exist today are the result of evolution towards more refined cells. and There are many details in cell evolution that cannot yet be explained.